La presencia alemana en costa rica durante la era del nacionalsocialismo (1933-1941) - Arias Mora, Dennis F. (2006)
The article studies the presence of Germans during the nazism age, and its role in the acceptance and diffusion of this phenomenon in Costa Rica's society. For this, the article analyzes the trajectory and social prestige of this community before the nazi era, and its relationship with the nazi movement during the Third Reich. Such issues are relate with the well known "fifth column" myth that prevails in the national historical research around the German immigrants, in order to reveal the conflicts inside this community. This approach emphasizes the political and cultural context of Costa Rica, during the consolidation of the Third Reich and the beginning of the Second World War.